Executive Systems Constrain the Flexibility of Online Control in Children During Goal-Directed Reaching - Ruddock, S.; Hyde, C.; Piek, Jan; Sugden, D.; Morris, Susan; Wilson, P. (Psychology Press, 2014)
We examined the influence of inhibitory load on online motor control in children. A sample of 129 school children was tested: younger, mid-age, and older children. Online control was assessed using a double-step perturbation paradigm across three trail types: non-jump, jump, and anti-jump. Results show that mid-aged children were able to implement online adjustments to jump trials as quickly as older children, but their performance on anti-jump trials regressed toward younger children. This suggests that rapid unfolding of executive systems during middle childhood may constrain the flexibility with which online control can be implemented, particularly when inhibitory demands are imposed.